Advanced signal processing on brain event-related potentials filtering ERPs in time, frequency and space domains sequentially and simultaneously - Cong, Fengyu; Ristaniemi, Tapani; Lyytinen, Heikki (World Scientific, 2015)
This book is devoted to the application of advanced signal processing on event-related potentials (ERPs) in the context of electroencephalography (EEG) for the cognitive neuroscience